Black leadership in education governance: a critical autoethnographic study of school board service - Coleman, Jurdene Arlette (My University, 2024)
There is limited scholarship on school boards and even less on the identity and experiences of those who serve on these citizen governance bodies. Through autoethnographic narrative inquiry, this study examines my experiences as a Black school board member in a predominately white school district in Kansas during the racial unrest of the early 2020s. In conceptualizing school boards as organizations, I illustrate the socio-material influence of systemic racism on school board process and practice in the form of white supremacist organizational values. Specifically, I examine how these values impacted my ability to represent my community as school board president. This study uses critical autoethnography to challenge the longstanding norms of school boards by amplifying my own concealed story and creating pathways to more just and inclusive spaces for Black school board members. Through this study, it became clear that my school board was not built to support the involvement of Black school board members as seen in my need to maintain a double consciousness as both a Black woman and the school board president, each with its own set of competing values. In response to the pervasiveness of white supremacist organizational values, I turn to the foundational practice of leadership-as-practice theory, expanding on the practice of stabilizing and developing critical approaches to the practice of stabilizing which provide concrete steps for increasing Black school board member participation and engagement in public school boards. The study concludes with a discussion of the challenges of using autoethnography to study this topic as well as ideas for future research to understand more about the perspectives and experiences of other Black school board members.
Keywords: Leadership as practice; Autoethnography; School board; Public school governance; Black women